Professor Colin Pearson: 'one of the most versatile and capable conservators of his generation'†. Issue 1 (2nd January 2018) - Scott, Marcelle
Abstract : Professor Colin Pearson played a transformative role in cultural materials conservation in Australia. As a founding member of the AICCM, the first Editor of its peer-reviewed journal, and the Head and Professor of the first tertiary conservation education program in Australia, Colin Pearson influenced the lives and careers of many conservators across Australia and further afield. This paper considers his extraordinary contributions, with a particular focus on conservation education, highlighting his many achievements and his legacy to the discipline and to the profession.